2003
DOI: 10.1590/s1516-35982003000600010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da perda endógena de aminoácidos, em função de diferentes níveis de fibra para suínos

Abstract: O experimento foi conduzido com o objetivo de avaliar as perdas ileais endógenas de aminoácidos, em função de diferentes níveis de inclusão de fibra em uma dieta isenta de proteína. Foram utilizados oito suínos mestiços, machos castrados, com peso médio inicial de 50,17 ± 4,10 kg, submetidos previamente à cirurgia para implantação de cânula "T" simples, distribuídos em um delineamento experimental de blocos ao acaso, com quatro tratamentos, quatro repetições e um animal por unidade experimental. Os tratamentos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
2
1
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
7
2
1
6
Order By: Relevance
“…Methionine and cystine presented the lowest endogenous losses, as previously observed by Wilson et al (1981), with channel catfish; Yamamoto et al (1998) These results may be partially explained by the lower content of sulfur amino acids both in the mucin layer and in pancreatic secretions compared with other amino acids (Pozza et al, 2003).…”
Section: Resultssupporting
confidence: 57%
“…Methionine and cystine presented the lowest endogenous losses, as previously observed by Wilson et al (1981), with channel catfish; Yamamoto et al (1998) These results may be partially explained by the lower content of sulfur amino acids both in the mucin layer and in pancreatic secretions compared with other amino acids (Pozza et al, 2003).…”
Section: Resultssupporting
confidence: 57%
“…The values for endogenous losses obtained in this study were relatively low for methionine and cystine, which can be explained partly by the low content of sulfur amino acids, both in the mucin layer and pancreatic secretions, as compared to other amino acids (Pozza et al, 2003).…”
Section: Resultscontrasting
confidence: 49%
“…The values of total amino acids of CM (Table 5) were similar to those reported by Rojo et al (2001), who found values of lysine (19.6 g/kg), threonine (15.5 g/kg), tryptophan (4.6 g/kg), met+cys (16.4 g/kg), isoleucine (13.8 g/kg) and leucine (25.2 g/ kg) in the data studied with a compilation of 171 aminograms of CM.…”
Section: Resultssupporting
confidence: 86%
“…Minkowski (2002) attributed the reduction of AIDC and TIDC of CM to its high fiber content. Likewise, Pozza et al (2003) showed that the canola fiber (NDF) considerably influenced the ileal endogenous losses of nitrogen in pigs, since these compounds are not digested by intestinal enzymes.…”
Section: Resultsmentioning
confidence: 99%